A Clinically Relevant Protocol Induces Tolerance to a Vascularized Composite Allograft Across Major Histocompatibility Barrier In A Large Animal Model. (July 2018) - Mathes, David; Swearingen, Bruce J; Graves, Scott S; Storb, Rainer
Abstract : Introduction: Vascularized Composite Allograft (VCA) transplantation is a clinical reality but its widespread application is limited by the need for chronic immunosuppression. We have developed a clinically relevant protocol based on non-myleoablative bone marrow transplantation platform. One barrier has been the need for the time required to pre-conditioning the recipient thereby limiting these protocols to living transplants. We have developed a protocol that uses a rapid stem cell mobilizer (AMD3100) that can mobilize cells in 6 hours after administration and combined that with our previously described protocol. Methods: 7 DLA-haploidentical, recipients [Group I] received conditioning with 350cGy total body irradiation (TBI), AMD3100 mobilized donor stem cells, bone marrow aspirate, and VCA transplantation and a limited course of post-grafting immunosuppression (Mycophenolate Mofetil (MMF) 56 days/Cyclosporine (Csp): 70 days). 3 DLA-mismatched recipients [Group 2] received conditioning with 450cGy TBI, AMD3100 mobilized donor stem cells, bone marrow aspirate, and VCA transplantation with post-grafting immunosuppression (MMF 56 days, CSP, 70 days). We also added 28 days Rapamycin to increase the T regulatory cell population. Donor cell chimerism was evaluated by PCR and allograft survival was followed clinically and histologically. Results: Initial stem cell engraftment and donor chimerism were seen in all animals. Group 1 demonstrated tolerance to the transplants and engraftment off immunosuppression (POD 426, 265, 176, 131, 95). Two animals had pulmonary issues and were sacrificed before the cessation of immunosuppression (POD 59, 45). One dog lost donor cell chimerism at POD 70 and had a single rejection episode of the skin (POD 79) that resolved and has since gone on to maintain tolerance to the VCA (POD 176). Group 2 demonstrated donor cell engraftment and tolerance (figure 2.) to the VCA (H910 POD 93, H912 POD 73). The most recent chimerism levels are H910 52.9% Granulocytes and 85.4% Lymphocytes and H912 26.7% Granulocytes and 53.4% lymphocytes. The third dog is on-going with good initial engraftment. Conclusions: This is the first clinically relevant protocol to induce tolerance in a large animal model across both a haploidentical and now a complete mismatches. This protocol can be completed with out the need for preconditioning and is applicable for cadaveric transplantation as the AMD3100 can be given to a brain-dead organ donor and the cell mobilized in 6 hours.